A Frequency Analysis Method to Estimate the Relative Importance of Basset Force on Small Particles in Turbulence. (June 2021) - Li, Zhenzhong; Wei, Jinjia; Bu, Shanshan; Yu, Bo
Highlights: A frequency analysis method is developed and verified to estimate the relative importance of Basset force. Characteristic frequency of the particle relative velocity is estimated by an analogy method and the Fourier analysis. Amplitude of the Fourier transformation of the relative velocity has a peak when the particle Stokes number is small. Abstract: The correct calculation of interphase forces exerted on particles is important for particle tracking and interphase interaction. The Basset history force, which accounts for unsteady drag effects, is often neglected in simulations because its calculation is very demanding in CPU time and memory requirements. Thus, it is significant to approximately estimate the relative importance of the Basset force before implementing relevant numerical simulations. In the present study, a frequency analysis method based on the characteristic frequency is developed to estimate the importance of the Basset force relative to the drag force. Both an analogy method and the Fourier analysis are used to estimate the characteristic frequency of the particle relative velocity. Then the frequency analysis method is verified by comparing the predicted values with the statistical values of the direct numerical simulations on the particle-laden channel turbulence. Within a wide range of particle parameters, the relative importance of the Basset force predicted by the frequency analysis method, both by the analogy method and via the Fourier analysis, agrees with that obtained from the direct numerical simulation. Although the amplitude of the Fourier transformation of the particle relative velocity reduced rapidly along with the dimensionless frequency, in cases where the particle Stokes number was not very large, it had a small but considerable peak under the dimensionless frequency from 1 to 1.6. This is caused by the interaction between light particles and the Kolmogorov dissipation vortex. It was also found that the Basset force was significant relative to the drag force in most cases of the present study.